Study of corrosion inhibition of coupled Al2Cu–Al and Al3Fe–Al by cerium cinnamate using scanning vibrating electrode technique and scanning ion-selective electrode technique. (September 2015) - Shi, Hongwei; Han, En-Hou; Liu, Fuchun; Wei, Tao; Zhu, Zhengwang; Xu, Daokui
Highlights: The corrosion inhibition of coupled Al2 Cu–Al and Al3 Fe–Al by cerium cinnamate was studied. SVET and SIET were used to study the distribution of current densities and pH. The corrosion inhibition mechanisms were analyzed. Abstract: The galvanic corrosion of the coupled Al2 Cu and Al as well as Al3 Fe and Al in 0.005 M NaCl in and without the presence of cerium cinnamate was studied. Scanning vibrating electrode technique and scanning ion-selective electrode technique were used to measure the distribution of current densities and pH. The results indicate that cerium cinnamate played inhibiting effect on the coupling corrosion of Al2 Cu–Al and Al3 Fe–Al. For Al2 Cu–Al, the inhibition was mainly influenced by the production of cerium oxide/hydroxide on Al2 Cu surface. However, for Al3 Fe–Al, the inhibition was mainly influenced by the adsorbed cerium cinnamate on the Al3 Fe surface.